1988
DOI: 10.1084/jem.167.4.1281
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene production in human neutrophils primed by recombinant human granulocyte/macrophage colony-stimulating factor and stimulated with the complement component C5A and FMLP as second signals.

Abstract: Neutrophils (PMN) preincubated with recombinant human granulocyte/macrophage colony-stimulating factor (rhGM-CSF) for 2 h and then stimulated with the chemotactic factors, C5a or FMLP, produce substantial amounts of the lipoxygenase products 5-Hete, LTB4, and omega-oxidised LTB4 metabolites (4.36 +/- 0.95 (SEM) pM (n = 21) LTB4 and LTB4 metabolites/10(6) PMN). No lipoxygenase metabolites are detected by HPLC and RIA if purified PMN are stimulated by either GM- CSF or chemotactic factors in the absence of exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(83 citation statements)
references
References 42 publications
8
74
1
Order By: Relevance
“…Apparently, excessive amounts of exogenous AA (30-250 1.M) are necessary in order to obtain significant production of LTB4 or its metabolites following PMNL stimulation with chemotactic factors (25,26,40). Moreover, it has been demonstrated that AA itself is able to activate PMNL-5-LO at high concentrations when given in ethanolic solution (41), possibly due to membrane perturbation, increased trans-membrane penetration of AA (42), or induction of additional cellular AA release by the vehicle (43).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, excessive amounts of exogenous AA (30-250 1.M) are necessary in order to obtain significant production of LTB4 or its metabolites following PMNL stimulation with chemotactic factors (25,26,40). Moreover, it has been demonstrated that AA itself is able to activate PMNL-5-LO at high concentrations when given in ethanolic solution (41), possibly due to membrane perturbation, increased trans-membrane penetration of AA (42), or induction of additional cellular AA release by the vehicle (43).…”
Section: Resultsmentioning
confidence: 99%
“…GM-CSF-treated or 'primed' PMNL show increased functional responses to a second stimulation, such as enhanced superoxide anion formation and enzyme release in response to FMLP (Weisbart et al, 1987;Kaufman et al, 1989), increased phagocytosis (Lopez et al, 1986) and also increased leukotriene synthesis in response to soluble agonists (FMLP, C5a, PAF) and the ionophore A23187 (Silberstein et al, 1986;Dahinden et al, 1988;Dipersio et al, 1988). In the present study, GM-CSF-priming of PMNL led to the expected increase of leukotriene synthesis in response to FMLP (Figures 2a and 3).…”
Section: Discussionmentioning
confidence: 99%
“…The use of C5a and FMLP allowed us to detect macrophage colony-stimulating factor [29][30][31][32], tumor necrosis factor-a [33], and endotoxin [10,11,28], have been shown to enhance the response triggered by a second agonist. Priming with EAS occurs rapidly (figure 3), whereas prolonged incubation is required for the action of lipopolysaccharide or cytokines [7,10,11,28].…”
Section: Discussionmentioning
confidence: 99%